Investigation into marine traffic and a risky area in the Turkish straits system: Canakkale strait - Basar, Ersan (Transport, 2010)
The Turkish Straits comprising the Strait of Canakkale, the Strait of Istanbul and the Sea of Marmara are unique in many respects. All dangers and obstacles characteristic of narrow waterways are present and acute in this critical sea lane. This research reveals the simulation of Canakkale (Dardanelle) Strait under different traffic conditions and identifies risky areas. The results of this simulation show that an increase of 25% in the existing traffic grows 43 times in the number of waiting ships (from 1.663 to 73.73), whereas waiting time increases 29 times (from 24.267 to 737.07). As a result of simulations and risk analysis, it is found that Nara turning point is the bottleneck point of the strait due to its topographic structure and the current system. First published online: 27 Oct 2010